THE ECLECTIC USE OF THE PROCESS AND THE GENRE APPROACHES THROUGH THE IMPLEMENTATION OF FOURSQUARE TECHNIQUE IN TEACHING EFL WRITING - Eko Windu Prasetya (Universitas Bandar Lampung, 2019)
This paper proposes a technique, namely Four Square, that the teachers can implement as an answer to the basic challenge in teaching English as a Foreign Language (EFL) writing, that is to shape the learners to be more creative and productive in writing. The introduction of Four Square, mainly aims at the learners’ ability in creating written texts which are grammatically accurate and functional in social context. The significant characteristic of Four Square to the development of learners’ writing skill is the fact that it applies the process and genre approaches at the same time. The two approaches are necessary in making the learners more thoughtful in the sense of their creativity in expressing ideas and of their understanding of readership. In Four Square, the learners consider the steps of writing; exploring idea, prewriting, organizing, writing first draft, revising draft, and producing the final copy, as well as consider the readership; the audience, purpose, and social function of the writing they produced. Thus, Four Square will bring the learners to the sufficient and effective path of writing process and will enable them to write more meaningful to the readership.